Poster 153: Dynamic Radiographic Evaluation of Scapulohumeral Rhythm in Patients with Massive vs Small Rotator Cuff Tears. Issue 7 (30th July 2022) - Xiao, Angel; McGinley, Beau; Ahmed, Adil; Gottschalk, Michael; Wagner, Eric
Objectives: The management of rotator cuff tears varies based on patient age, function, tear size, and chronicity. Treatment of massive tears results in less favorable or predictable outcome, presenting a challenge in determining the optimal intervention. Classification of a tear as "massive" is often based on MRI and confirmed intraoperatively. However, the use of a functional measure of shoulder motion, such as the scapulohumeral rhythm (SHR), offers an alternate, clinically relevant method to help guide diagnosis and surgical management. Defined as the ratio of glenohumeral (GH) to scapulothoracic (ST) motion, SHR is known to be altered in patients with rotator cuff tears. While previously challenging to measure SHR in a clinical setting, a novel technique known as Dynamic Digital Radiography (DDR) provides a safe and cost-effective method to directly compare changes in motion between patients with rotator cuff tears and correlate these changes to tear severity. The purpose of this study was to evaluate patients with massive and small rotator cuff tears using DDR, assessing for differences in SHR and range of motion between the two groups. Methods: Shoulders were prospectively analyzed using DDR via obtaining a series of pulsed radiographs at up to 15 Hz of the joint in motion. Scapulothoracic motion and glenohumeral motion were quantified based on the DDR images (figure 1). Measurements were taken in humeral abduction at 0-30°, 30-60°, 60-90°, and full abduction using the Grashey view. SHR at different points was calculated by dividing the humeral arc of motion by the scapular arc of motion in each of those motion ranges. Pairwise t-tests were performed on the obtained data to compare differences between groups at an α level of 0.05. Results: 42 patients with a primary diagnosis of rotator cuff tear matched for age and BMI were analyzed (table 1). Based on clinical presentation and MRI, 29 patients were classified as massive rotator cuff tear (MRCT) and 13 patients were classified as small rotator cuff tear (SRCT). The final angle calculations are displayed in table 2. SRCT patients had a significantly higher average overall SHR of 3.04 ± 1.16 compared to the MRCT SHR of 1.91 ± 0.51 (p=0.003). When analyzed across 30-degree intervals of humeral abduction, MRCT patients had a significantly lower SHR compared to SRCT patients at 30-60° (1.83 ± 0.97 vs 3.39 ± 1.62, p=0.005). MRCT also had a lower SHR between 0-30° (2.63 ± 2.08 vs 4.74 ± 3.83, p=0.08) and 60-90° (2.13± 0.80 vs 2.91 ± 1.41, p=0.13) of humeral abduction compared to SRCT patients, but these differences were not statistically significant. SHR changes across these intervals of humeral abduction are plotted in figure 2. Scapular range of motion during humeral abduction was lower in SRCT compared to MRCT (29.71 ± 12.91 vs 41.57 ± 10.41, p=0.08). No statistically significant difference was found in humeral range of motion between MRCT (76.02 ± 22.66) and SRCT (80.93 ± 20.71). Conclusions: A dynamic measurement of motion demonstrates that scapulohumeral rhythm is significantly different between patients with small vs. massive rotator cuff tears. Based on DDR analysis, patients had a marked difference in the initiation of motion and through the first 60 degrees of humeral abduction, resulting in a nearly 2x lower SHR in MRCT compared to SRCT. Moreover, evaluation of glenohumeral and scapulothoracic motion during humeral abduction demonstrated that patients with larger tears had an increased reliance on scapular contributions to overall humeral elevation. Dynamic measurement of SHR represents a novel method for evaluating rotator cuff tears, with marked differences noted in the earlier phases of shoulder motion. Further study and validation of the dynamic assessment of SHR has the potential to augment the diagnostic algorithm for rotator cuff tears, and ultimately inform prognostic and functional expectations for both the patient and the physician. Table 1. Patient Demographics Table 2. Relative contributions by glenohumeral (GH) and scapulotlioracic (ST) joint to shoulder girdle motion Figure 1. Reference lines used for calculation of the humeral and scapular abduction arcs. Measurements were taken in reference to a vertical line. Calculations were made in the neutral position, at initiation of abduction, 30°, 60°, 90° and full abduction. Figure 2. SHR measured at 30-degree intervals of humeral abduction. The * Indicates a statistically significant difference at α = 0.05 in SHR measured between massive rotator cuff tear and small rotator cuff tear patients. P-values from left to right are 0.08 (0-30 °), 0.005 (30-60 °), 0.13 (60-90 °), and 0.003 (total)